2017
DOI: 10.1590/0103-8478cr20160780
|View full text |Cite
|
Sign up to set email alerts
|

Essential oils in the control of dry bubble disease in white button mushroom

Abstract: Lecanicillium fungicola, which causes Dry bubble disease, induces infections and inflicts major losses in champignon production. The control can be managed through measures of hygiene and use of fungicides; however, in Brazil there are no registered products. This study aimed to estimate the influence of various essential oils extracted from Melissa officinalis, Thymus vulgaris, Origanum vulgare, Eucalyptus globulus, Cinnamomum zeylanicum and Syzygium aromaticum on the in vitro development and their uses. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
1
4
0
1
Order By: Relevance
“…cordycipiticola can be cultured on artificial media besides mycoparasitism, but no morphologic alteration of C. militaris was observed when the dual culture of C. militaris and C. cordycipiticola on PDA plates was performed (Figure S6). The same results were observed with dual culture between A. bisporus and L. fungicola [96], A. bisporus and H. perniciosus [97]. It was suggested that the interactions between mushrooms and pathogens on plates (pythogenesis) are different from infecting on the fruiting bodies (mycoparasites).…”
Section: Discussionsupporting
confidence: 58%
“…cordycipiticola can be cultured on artificial media besides mycoparasitism, but no morphologic alteration of C. militaris was observed when the dual culture of C. militaris and C. cordycipiticola on PDA plates was performed (Figure S6). The same results were observed with dual culture between A. bisporus and L. fungicola [96], A. bisporus and H. perniciosus [97]. It was suggested that the interactions between mushrooms and pathogens on plates (pythogenesis) are different from infecting on the fruiting bodies (mycoparasites).…”
Section: Discussionsupporting
confidence: 58%
“…fungicola (PTCC: IRAN 2270C) was isolated from a diseased A. bisporus fruiting body from Tehran, Iran, in 2014. The mycoparasites were maintained in PDA medium under refrigeration and re‐cultured every 1 month (dos Santos et al, 2017). One protective bead of L. fungicola was located in the middle of PDA medium and incubated at 20°C for 7 days or until an adequate growth occurred (Stanojević et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the fungitoxic effect observed in vitro against L. fungicola and the results achieved showing a better response of aerated compost tea from SMC in comparison to prochloraz-Mn to prevent dry bubble disease in crop trials [ 54 ] suggest that the application of compost teas could be a suitable alternative to common fungicides. In addition to compost teas, EOs from aromatic plants have also shown fungitoxic effect in plate (cinnamon, thyme, and clove oils were the most effective in inhibiting the mycelial growth and conidia germination of L. fungicola ) and effectiveness in crop applications (particularly effective in application after infestation) [ 56 ]. However, the selectivity of EOs towards the parasite is reduced and all the EOs tested by Geösel et al [ 76 ] caused damage in the crop, inhibiting the growth of host mycelium and causing necrotic spots on mushroom caps.…”
Section: Dry Bubble ( Lecanicillium Fungicola )mentioning
confidence: 99%
“…Oil treatments prevent pathogenic conidia germination when applied post-infection probably due to the presence of phenolic compounds in their composition. Dos Santos et al [56] Inhibitory and fungicidal activity of two EOs, cinnamon (Cinnamomum verum) and clove (Syzygium aromaticum) tested by microdilution, macrodilution fumigant, and macrodilution contact method.…”
Section: Soković and Vanmentioning
confidence: 99%